2020
DOI: 10.1021/acs.jafc.9b07816
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Coupled Electron Transfers of Defense Phytochemicals in Sorghum (Sorghum bicolor (L.) Moench)

Abstract: Sorghum (Sorghum bicolor (L.) Moench) produces a range of defense phytochemicals containing a quinone core structure: sorgoleone allelochemical, flavonoid phytoalexins, and a broad spectrum of polyphenols. Those phytochemicals react with the components of cellular and agroecosystems to form stable semiquinone radicals engaging in different proton-coupled electron transfer reactions. This unique redox reactivity of plant phenolics could be used to develop bioactive food ingredients and green pesticides. To achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…There is still a lack of mechanistic understanding in the anti-obesity activity of sorghum phenolic compounds and its components. In addition, the level of phenolic compound content is affected by several factors including the sorghum genotype, environmental stress, and extraction methods [ 15 ]. While such findings are of great value to human health, they lack information regarding the mechanism of function and fail to identify a sorghum genotype(s) with a high amount of relevant bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…There is still a lack of mechanistic understanding in the anti-obesity activity of sorghum phenolic compounds and its components. In addition, the level of phenolic compound content is affected by several factors including the sorghum genotype, environmental stress, and extraction methods [ 15 ]. While such findings are of great value to human health, they lack information regarding the mechanism of function and fail to identify a sorghum genotype(s) with a high amount of relevant bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Some sorghum accessions have a higher total phenolic content and more antioxidant compounds than those in other food sources [ 15 , 16 ]. However, the level of phenolic compounds is affected by several factors, including the sorghum genotype, environmental stress, and processing and extraction methods [ 17 ]. While such findings are of great value to the American public and to the sorghum community, there remains a lack of information regarding mechanisms and a failure to identify a sorghum genotype(s) with a high amount of relevant bioactive compounds for cultivation in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the herbicidal activity of sorgoleone has been attributed to the inhibition of photosynthesis and ATP turnover. 13,14 Iris plants are rich sources of bioactive secondary metabolites (more than 100 flavonoids, xanthones, and iridals). 15−17 antioxidant, antimicrobial, and anticancer effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, some Myrsinaceae and Iridaceae plants produce unusual alkylbenzoquinones. Although the detailed modes of action of such alkylbenzoquinones have been scarcely reported, several studies have indicated that these activities may be related to the redox properties of quinones with biological electron transport systems. For example, the herbicidal activity of sorgoleone has been attributed to the inhibition of photosynthesis and ATP turnover. , …”
Section: Introductionmentioning
confidence: 99%